The Relationship between Spiritual Intelligence and Fatigue and Moral Distress in Emergency Nurses: A Cross-Sectional Study - Seyed Hossein Shahcheragh; Nazanin Fekri; Mostafa Rad (Iranian Journal of Nursing and Midwifery Research)
Background: Emergency nurses face various challenging conditions and many moral distress that may associated with fatigue from providing care. The spiritual intelligence of nurses has been found to have an impact on the quality of care. This study aimed to investigate the relationship between the spiritual intelligence of emergency nurses with fatigue from providing care and moral distress in emergency nurses. Materials and Methods: This descriptive-analytical cross-sectional study was conducted on 200 nurses working in the emergency departments of hospitals in Semnan and Sabzevar, who were selected by stratified random method. They were asked to complete the spiritual intelligence, nurse fatigue scale, and moral distress questionnaire through self-reporting. The data were analyzed using SPSS 26 and Amos software, path analysis, and correlation tests. Results: An increase in spiritual intelligence leads to a significant reduction in moral distress (p = 0.01) and fatigue from caregiving (p = 0.001). In contrast, an increase in moral distress leads to a considerable increase in fatigue from caregiving (p = 0.001). Conclusions: The results showed that spiritual intelligence has an inverse relationship with moral distress and fatigue from providing care. Moral distress has a direct relationship with fatigue from providing care. Therefore, interventions in the field of increasing spiritual intelligence and reducing moral distress and fatigue from providing care are recommended.